2014
DOI: 10.1002/jat.2992
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biomarkers of phospholipidosis in rat blood and heart after amiodarone treatment

Abstract: Phospholipidosis (PLD) is characterized by an intracellular accumulation of phospholipids in lysosomes and concurrent development of concentric lamellar bodies. It is induced in humans and in animals by drugs with a cationic amphiphilic structure. The purpose of the present study was to identify a set of molecular biomarkers of PLD in rat blood and heart, hypotheticallya pplicable in preclinical screens within the drug development process. A toxicological study was set up in rats orally treated up to 11 days w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In addition, in liver tissue from Hexb / mice and DIPL rats, a striking remodeling of the Cer content was detected. Although an alteration of sphingolipid metabolism has been hypothesized (59), it is the first time, to our knowledge, that Cer concentrations have been shown to be affected in DIPL. Changes in Cer concentrations have been linked to many diseases, including neurodegenerative diseases such as Alzheimer's disease (60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, in liver tissue from Hexb / mice and DIPL rats, a striking remodeling of the Cer content was detected. Although an alteration of sphingolipid metabolism has been hypothesized (59), it is the first time, to our knowledge, that Cer concentrations have been shown to be affected in DIPL. Changes in Cer concentrations have been linked to many diseases, including neurodegenerative diseases such as Alzheimer's disease (60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 87%
“…However, arachidonic acid may be lowered as result of down‐regulation of Pla2g2e (log2 fold change = −1.74). It was reported that the occurrence of cardiovascular disease is closely related to Pla2g2a .…”
Section: Resultsmentioning
confidence: 99%
“…BMP increase in cells and tissues was reported in various disorders such as cationic amphiphilic drugs (CAD)-induced phospholipidosis and genetic lysosomal storage diseases (LSDs) associated with endolysosomal dysfunction characterized by accumulation of undigested material and secondary metabolites [27][28][29][30][31]. The CAD toxicity, a major concern in drug development, is linked to this build-up of drug and undigested compounds inside the acidic endolysosomal compartment visualized by the formation of vacuoles and concentric multi-lamellar inclusions [32,33].…”
Section: Introductionmentioning
confidence: 99%